Question prompt lists and endorsement of question‐asking support patients to get the information they seek—A longitudinal qualitative study. (26th April 2022) - Tracy, Marguerite; Ayre, Julie; Mac, Olivia; Copp, Tessa; Trevena, Emerita Lyndal; Shepherd, Heather
Abstract: Introduction: Question prompt lists (QPLs) have been found to support patients to ask questions and improve the information they receive from doctors. However, some QPL tools, which have been available online for almost 15 years, have little published data on their impact in real‐world settings. This study's aim was to understand patients' attitudes and experiences accessing health information and to assess the impact of introducing two generic QPLs over 3 months. Methods: A longitudinal qualitative study consisting of three semi‐structured interviews over a three‐month period was conducted with 31 purposively selected participants, adults ≥18 years, recruited online and through social media. Participants were introduced to two different QPLs currently available online ('Question Builder'; 'AskShareKnow'). Inductive thematic analysis of a total of 92 semi‐structured telephone interviews was conducted during May–November 2020. Results: Three main themes are described. (1) Participants described barriers and facilitators to accessing health information: navigating a complex health system; difficulty asking questions of their healthcare professionals and that they value doctors with good communication skills. (2) QPLs helped some participants recognize the role of question‐asking in consultations, made them feel more empowered and helped them prepare and prioritize. (3) Participants wanted QPLs to be easier to use, be accessible when needed and that question‐asking and QPLs should be normalized in medical consultations. Conclusions: Well‐designed and easily accessible QPLs can empower people to ask questions and be more involved in decisions about their health care. Endorsement of question‐asking in consultations by healthcare professionals and providing QPL tools at the point of contact with health services will be key to realizing the potential of QPLs. Patient or Public Contribution: This study was completed in conjunction with a reference group consisting of a consumer representative, representatives from the Australian Commission on Safety and Quality in Health Care, Healthdirect Australia Ltd., and the research team.